2018
DOI: 10.1021/acs.jpcc.8b03804
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dopant–Host Energy Level Offset on Thermoelectric Properties of Doped Organic Semiconductors

Abstract: Increasing the amount of charge carriers by molecular doping is important to improve the function of several organic electronic devices. In this work, we use highly fluorinated fullerene (C 60 F 48) to p-type dope common amorphous molecular host materials. We observe a general relation between the material's electrical conductivity and Seebeck coefficient, both strongly depending on the energy level offset between amorphous host and dopant. This suggests that the doping efficiency at similar doping levels is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…Doping efficiency is expected to increase with the energetic offset between the polymer HOMO and dopant LUMO. [2,46,47] Yet, to date, few papers have been able to pin down exactly how the electronic offset affects doping efficiency largely because of the problems inherent in disentangling structural from electronic effects. In previous studies, either only slight tuning of the dopant oxidation potential was possible (while maintaining an energetic offset large enough to dope), [21,48,49] or significant structural changes of the dopant were necessary to more dramatically tune the oxidation potential, [6,46,49,50] which in turn changes the Coulomb interaction between the counterion and doped carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Doping efficiency is expected to increase with the energetic offset between the polymer HOMO and dopant LUMO. [2,46,47] Yet, to date, few papers have been able to pin down exactly how the electronic offset affects doping efficiency largely because of the problems inherent in disentangling structural from electronic effects. In previous studies, either only slight tuning of the dopant oxidation potential was possible (while maintaining an energetic offset large enough to dope), [21,48,49] or significant structural changes of the dopant were necessary to more dramatically tune the oxidation potential, [6,46,49,50] which in turn changes the Coulomb interaction between the counterion and doped carriers.…”
Section: Introductionmentioning
confidence: 99%
“…As described in the Experimental section, the parameters for the different device structures were kept constant but for the 10 nm thick doped (5 Â 10 17 p-type) layer that was positioned either 10 nm or 25 nm away from the junction. Using the absorption of the chargetransfer (CT at $700 nm) to estimate the doping efficiency of C 60 F 48 as a function of the host ionization energy 54 suggests that the doping may be as high as 10 19 cm À3 . Interestingly, it was shown that the fraction of CT that dissociates into free charges could be as low as 10% of the values extracted through absorption.…”
Section: Device Simulationsmentioning
confidence: 99%
“…However, the characteristically low doping efficiencies and microstructural disruption of the host semiconductor upon introduction of the often bulky molecular dopants are two effects that have so far inhibited widespread adoption of the technology in OTFTs . A further limitation is the fact that although numerous studies have been performed on p‐type doping of OSCs, research on n‐type dopants is rather limited . This is because doping via the traditional ground‐state integer charge transfer (ICT) process requires the donation of an electron from the highest occupied molecular orbital (HOMO) of the dopant, to the lowest unoccupied lower orbital (LUMO) of the host semiconductor.…”
Section: Introductionmentioning
confidence: 99%